Study of High Potential for Addiction Group 1 Psychotropic Drugs Used in Science - Yuneka Saristiana; Fendy Prasetyawan; Ratna Mildawati; Chandra Arifin; Faisal Akhmal Muslikh; Abd Rofiq; Widhi Astutik (Journal of Advanced Pharmaceutical Research Sciences and Sustainability (JAPRSS), 2026)
Background. Research on high-potential addiction psychotropic drugs from Group 1 is an essential undertaking in the fields of pharmacology and mental health treatment, requiring an extensive introduction to provide context and delineate its importance and breadth. Purpose. This study offers a comprehensive examination of Group 1 psychotropic drugs, emphasizing their pharmacological characteristics, addictive tendencies, and regulatory implications Method. Drawing upon data extracted from Indonesian Ministry of Health Regulation No. 10 of 2022, the research compiles and delineates the psychotropic drugs falling under Group 1 classification. Results. Drugs name as Deskloro ketamin, 2F- Deskloro ketamin, Flubroma zolam, Flualpra zolam, Klonazolam are identified, each presenting distinct pharmacological effects and addiction potentials. The study highlights the imperative for stringent regulatory measures owing to the pronounced likelihood of abuse and adverse consequences associated with these substances. Regulatory frameworks must remain dynamic to effectively address emerging challenges and evolving patterns of drug usage. Conclusion. This research significantly contributes to the comprehension of psychotropic drugs and informs strategies aimed at ensuring their judicious and safe utilization.